Evaluation of the Immunomodulatory Activities of the Probiotic Strain Lactobacillus fermentum UCO-979C - Garcia-Castillo, Valeria; Komatsu, Ryoya; Clua, Patricia; Indo, Yuhki; Takagi, Michihiro; Salva, Susana; Islam, Md. Aminul; Alvarez, Susana; Takahashi, Hideki; Garcia-Cancino, Apolinaria; Kitazawa, Haruki; Villena, Julio (Frontiers in Immunology, 2019)
Lactobacillus fermentum UCO-979C, a strain isolated from a human stomach, was previously characterized by its potential probiotic properties. The UCO-979C strain displayed the ability to beneficially regulate the innate immune response triggered by Helicobacter pylori infection in human gastric epithelial cells. In this work, we conducted further in vitro studies in intestinal epithelial cells and in vivo experiments in mice in order to characterize the potential immunomodulatory effects of L. fermentum UCO-979C on the intestinal mucosa. Results demonstrated that the UCO-979C strain is capable to differentially modulate the immune response of intestinal epithelial cells triggered by Toll-like receptor 4 (TLR4) activation through the modulation of TLR negative regulators’ expression. In addition, we demonstrated for the first time that L. fermentum UCO-979C is able to exert its immunomodulatory effect in the intestinal mucosa in vivo. The feeding of mice with L. fermentum UCO-979C significantly increased the production of intestinal IFN-γ, stimulated intestinal and peritoneal macrophages and increased the number of Peyer’s patches CD4+ T cells. In addition, L. fermentum UCO-979C augmented intestinal IL-6, reduced the number of immature B220+CD24high B cells from Peyer´s patches, enhanced the number of mature B B220+CD24low cells, and significantly increased intestinal IgA content. The results of this work revealed that L. fermentum UCO-979C has several characteristics making it an excellent candidate for the development of immunobiotic functional foods aimed to differentially regulate immune responses against gastric and intestinal pathogens.